Former farm workers of foreign descent in communal areas in post-fast track Zimbabwe : the case of Shamva District - Chadambuka, Patience (Rhodes University, Faculty of Humanities, Department of Sociology)
Land and ethnicity continue to condition contestations in relation to belonging amongst rural Zimbabweans. The colonial era defined Zimbabwe's land politics in a highly racialised and ethnicised manner. Racially, the colonial era gave birth to white-owned fertile farm lands, while blacks (or Africans) were resettled in agriculturally-unproductive Reserves, later referred to as communal areas in the post-colonial era. Though they were initially created with a segregatory and oppressive intent bent on disenfranchising native Africans, the Reserves became a definitive landscape embedded in ethnic and ancestral belonging for the autochthonous Natives. The Reserves were created exclusively for autochthonous Africans, and the colonial administration ensured that foreign migrant Africans recruited mainly as covenanted labour from nearby colonies would not be accommodated and consequently belong in Reserves. Migrant Africans were instead domiciled in white commercial farms, mines and urban areas, and deprived of land rights accorded to the autochthones. In the case of white farms specifically, the labourers experienced a conditional belonging (to the farm). This overall exclusionary system was later inherited and maintained by the post-colonial Zimbabwean government, up until the year 2000. Zimbabwe's highly documented Fast Track Land Reform Programme (FTLRP) from the year 2000 did away with the entrenched racial bifurcations of land, as white commercial farms became fast track farms. However, it did not undercut the existence of communal areas. The FTLRP had a profound effect on the lives of commercial farm workers, particularly those of foreign origin who had no other home or source of livelihood to fall back on after fast track displacements. Some though sought to move into communal areas, from which they had been excluded previously. Within this context, most scholarly studies of the post fast track period ignore the plight of former farm workers especially those that moved to, and into, communal areas. This ethnographic study, specifically of former farm workers of foreign origin in Shamva communal areas, therefore seeks to contribute to Zimbabwean studies in this regard. It documents and examines the perceptions, practices and lived experiences of former farm workers of foreign origin now residing in the Bushu communal areas of Shamva, and how they interface with Bushu autochthones in seeking to belong to Bushu. This is pursued by way of qualitative research methods (including lengthy stays in the study sites) as well as through the use of a theoretical framing focusing on lifeworlds, interfaces, belonging, othering and strangerhood. Key findings reveal that belonging by the former farm workers in Bushu entails a non-linear and convoluted process characterised by a series of contestations around for instance land shortages, limited livelihood strategies and cultural difference. This project of belonging does not entail assimilation on the part of the former farm workers, as they continue to uphold certain historical practices, leading to a form of co-existence between the autochthones and allochthones in Bushu. In this way, the former farm workers seem to develop a conditional belonging in (and to) Bushu, albeit different than the one experienced on white farms in the past.
Keywords: Migrant agricultural laborers -- Zimbabwe -- Shamva District; Agricultural laborers, Foreign -- Zimbabwe -- Shamva District; Land reform -- Zimbabwe; Belonging (Social psychology) -- Zimbabwe -- Shamva District; Social integration-- Zimbabwe -- Shamva District; Fast Track Land Reform Programme (FTLRP)